Substitution of a commercial diet with raw meat complemented with vegetable foods containing chickpeas or peas affects faecal microbiome in healthy dogs. Issue 1 (2nd January 2019) - Sandri, Misa; Sgorlon, Sandy; Conte, Giuseppe; Serra, Andrea; Dal Monego, Simeone; Stefanon, Bruno
Abstract: The aim of the study was to investigate if the inclusion of chickpeas or peas in the diet can modify faecal microbiome in dogs. Eight healthy adult Border collie, fed a commercial extruded diet as reference diet (RD), were divided in two groups of four individuals. At the beginning of the trial, one group received a diet based mainly of raw meat, rice and chickpeas (CP) and in the other group this pulse was substituted with peas (PE). After 14 days, the dogs with CP diet shifted to the PE and those with PE shifted to the CP diet, for another 14 days. Faeces were collected at the beginning (T0), after 14 days (T14) and at the end of the study (T28). Faeces were analysed for 16S rRNA, short chain fatty acids (SCFA), lactate, pH and faecal score was also evaluated. The SCFA and lactate in the faeces were not affected by the inclusion of pulses, with the only exception of isovalerate, which was higher in CP and PE diets in comparison with RD diet ( p < .05). The abundances of Erysipelotrichaceae incertae sedis, Eubacterium, Anaerobacter and Sarcina significantly differed in CP and PE in comparison with RD. Moreover, the genera Prevotella, Lactobacillus, Alloprevotella, Suttarella varied significantly between CP and PE diets. The observed modifications of faecal microbioma were related not only to the change from RD to CP or PE, but also to the type of pulse, chickpeas or peas. However, long-term studies are required to investigate the implications that pulses can have for gut health. Highlights: Faecal quality and end products of fermentation were similar between diets. Faecal microbiota is affected by the type of pulse and raw meat inclusion. Thermally treated Chickpeas or Peas in the diet of dogs were safe, but further study are required.